2008
DOI: 10.1103/physreva.77.040701
|View full text |Cite
|
Sign up to set email alerts
|

Absolute cross sections for dissociative electron attachment to acetylene and diacetylene

Abstract: Absolute cross sections for the production of the two astronomy-relevant negative ions H u C w C − and H u C w C u C w C − by dissociative electron attachment to acetylene C 2 H 2 and diacetylene C 4 H 2 were measured ͑with a Ϯ25% error bar͒. Acetylene yielded the C 2 H − ion at an electron energy of 2.95 eV with a cross section of 3.6Ϯ 0.9 pm 2 and also the C 2 − ion at 8.1 eV with a cross section of 4.1Ϯ 1 pm 2 .Diacetylene yielded the C 4 H − ion at 2.5 eV with a cross section of 3.0Ϯ 0.8 pm 2 and at 5.25 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 25 publications
8
60
0
Order By: Relevance
“…Sharp Feshbach resonances were observed at 6.7, 6.8, and 7.0 eV in the yield of slow electrons [31]. A more diffuse core excited resonance was postulated to be at the origin of the 5.25 eV dissociative electron attachment band [11,32]. A broad (width ≈ 2 eV) shape resonance was postulated experimentally at 4.3 eV, based on enhancement of the C-H stretch vibration, and assigned as 2 u (or 2 g ) [11].…”
Section: Resultsmentioning
confidence: 99%
“…Sharp Feshbach resonances were observed at 6.7, 6.8, and 7.0 eV in the yield of slow electrons [31]. A more diffuse core excited resonance was postulated to be at the origin of the 5.25 eV dissociative electron attachment band [11,32]. A broad (width ≈ 2 eV) shape resonance was postulated experimentally at 4.3 eV, based on enhancement of the C-H stretch vibration, and assigned as 2 u (or 2 g ) [11].…”
Section: Resultsmentioning
confidence: 99%
“…44 However, Chantry (1969) found that electrons with near zero eV energy could attach to N 2 O and the yield of oxygen negative ions production has a broad peak extending from ~0.0 eV to ~1.2 eV. Another more intense peak for this reaction occurs at 2.2 eV (Chaney and Christophorou, 1969).Absolute cross sections for the production O − by DEA to O 2 and N 2 O were recently measured by May et al (2008). O 2 yielded the O − ion at electron energy 6.5 eV with a cross section of 126 × 10 −20 cm 2 while, the O − production from N 2 O occurs at 2.2 eV with a cross section of 830 × 10 −20 cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The C 3 H − 3 cross section in methylacetylene is approximately half of that of the corresponding cross section for the C 2 H − + H channel in acetylene (3.45 pm 2 when measured with the present method [1] or 3.8 pm 2 when measured with the total ion collection method [2]). The π * shape resonance in acetylene lies at 2.6 eV (as seen in vibrational excitation spectra) and the threshold for this DEA channel is 2.74 eV.…”
Section: A Region Of the π * Shape Resonancementioning
confidence: 94%
“…This dissociation into ground-state fragments is symmetry forbidden in linear geometry and the H atom follows an out-of-line trajectory as the bond stretches [5]. Such behavior, where the resonant state cannot dissociate in original geometry and distorts during the fragmentation, has been seen in a handful of molecules, for instance C 2 H 2 [1,5], C 4 H 2 [2,3], HCCCN [4], and chlorobenzene [11]. A related case is HCN [7,12], where the outgoing H atom tunnels through the barrier with symmetry lowering playing a limited role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation